Promoting Public Accountability as Public Value Through Waste Management System - Bayu Widhi Antari, Ni Putu (Iapa Proceedings Conference, 2024)
This research aims to explain how accountability as public value is promoted through waste management system. In terms of the research method, qualitative approach, specifically phenomenological research is utilized. Qualitative data collection techniques are conducted by in-depth interviews to head of Buduk Village Government, Head of Citizen Empowerment, the wife of village officials, waste bank management cadres, and waste collectors. Moreover, data is collected through observation surrounding the village and the waste storage area. Secondary data is collected through journal articles, government reports, and institution's report. Based on data analysis, Accountability as public value can be promoted by strengthen responsibility, responsiveness, and transparency in waste management system. Responsibility can be reinforced by obeying the regulation on the upper level of government and village government. Responsiveness of the village government can be strengthened through the roles of complain mechanism. Transparency can be improved by publishing the amount of saving each member to all waste bank member. Regarding manuscript value, this research describes the wicked problems in waste management not only in managing the waste bank, but also organic waste management to the final waste disposal site. This paper also provide the solution to strengthen accountability as public value.